PENGARUH PGPR (Plant Growth Promotion Rhizobacter) TERHADAP PERTUMBUHAN DAN HASIL KEDELAI PADA TANAH GAMBUT - jumadi2010, jumadi2010; dwizulfita, dwizulfita; achmadmulyadi, achmadmulyadi (Fakultas Pertanian Universitas Tanjungpura, 2016)
PENGARUH PGPR (Plant Growth Promotion Rhizobacter) TERHADAP PERTUMBUHAN DAN HASIL KEDELAI PADA TANAH GAMBUT ARTIKEL ILMIAH Oleh : JUMADI NIM. C51110011 FAKULTAS PERTANIAN UNIVERSITAS TANJUNGPURA PONTIANAK 2016 THE EFFECT OF PGPR (Plant Growth Promotion Rhizobacter)ON THE GROWTH AND YIELD OFSOYBEAN ON PEAT SOILJumadi1) Dwi Zulfita and Ahmad Mulyadi 2)1) students, 2)lecturers of Faculty ofAgriculture, University Tanjungpura.ABSTRACTSoybean is an important food crop as a source of vegetable protein. As food crops,100 grams soybean contains 330 calories, 35% protein, 18% fat, 35% carbohydrateand 8% water, the rest is composed of minerals and vitamins. This study aimed todetermine the effect ofdifferent types ofPGPR and kinds ofPGPR on the growth andyield of soybean in peat. Research using experimental methods with completelyrandomized design (CRD) consisting of7 treatment